Transfusion-related acute lung injury (TRALI) in two thalassaemia patients caused by the same multiparous blood donor - George J Kontoghiorghes (Mediterranean Journal of Hematology and Infectious Diseases)
Two separate episodes of transfusion-related acute lung injury (TRALI) in thalassaemia patients caused by red blood cell transfusions from the same multiparous blood donor are reported. Both cases had the same symptomatology and occurred 10-60 minutes of transfusion. The patients presented dyspnea, sweating, fatigue, dizziness, fever, and sense of losing consciousness. The chest x-ray showed a pulmonary oedema-like picture with both lungs filled with fluid. The patients were treated in the intensive therapy unit. They were weaned off the ventilator and discharged following hospitalization 7 and 9 days respectively. The TRALI syndrome was diagnosed to be associated with HLA-specific donor antibodies against mismatched HLA-antigens of the transfused patients. Haemovigilance improvements are essential for reducing the morbidity and mortality in transfused patients. Blood from multiparous donors should be tested for the presence of IgG HLA-Class I and –Class II antibodies before being transfused in thalassaemia and other chronically transfused patients.